A Nutraceutical Strategy to Slowing Down the Progression of Cone Death in an Animal Model of Retinitis Pigmentosa - Piano, Ilaria; D’Antongiovanni, Vanessa; Testai, Lara; Calderone, Vincenzo; Gargini, Claudia (Frontiers in Neuroscience, 2019)
Retinitis Pigmentosa (RP) is an inherited retinal dystrophy characterized by progressive degeneration of the visual cells and abnormalities in retinal pigment epithelium, the vision is lost slowly and the final outcome is total blindness. The primary mutation responsible for RP is in rod but subsequently cone photoreceptors are also affected. The main modality of photoreceptor cell death is activation of apoptosis pathway but the biological mechanism linking the primary degeneration of rod to the secondary death of cone is still poorly understood. Possible causes of the secondary cone death are oxidative stress and/ or release of toxic factors from dying rods. The aim of this study is to analyze the effect of nutraceutical molecules with antioxidant properties on the progression of the disease in an established animal model of RP, rd10 mice. We show that chronic treatment per os with a flavanone (naringenin) or a flavonol (quercetin) present in citrus fruits, grapes and apples, preserves retinal morphology and ameliorate functionality. These actions are associated with a significant reduction of stress-oxidative markers, such as the detoxifying enzymes Sod1 and Sod2. In addition, naringenin and quercetin treatment reduces the levels of acrolein staining associated with a reduction of ROS in the cellular environment. The study demonstrates the beneficial effects of naringenin and quercetin, two molecules that possess antioxidant properties, limiting neurodegeneration and thus preventing cone damage.